Jane Lawton: capstone - Lawton, Jane, artist (Colorado State University. Libraries, 2025)
The artist's statement: My work is an exploration of materials, as well as personal discovery relating to my relationships to my body and my family/family history. In the past few years I have been struggling with new-onset health issues that have strained my connection to my body; while also navigating a difficult relationship with my family. Within this same time frame, I have been researching my family going back about 100 years through family records and photo collection. Within this personal experience and research I have been struck by alarming patterns that connect me to these several generations of my family. From people pleasing to shame, and secrets, my family's generations have passed down a legacy of overt restraint. Always at the cost of oneself. I've been thinking about the idea of reincarnation through carrying on genes and what it means to be related by blood. In my work I've been utilizing chiffon curtains as a barrier that represents skins. Something to separate the interior to the exterior domestic and public. At the moment, my practice utilizes sound, performance, video, and ceramic and fiber sculpture in order to explore these connections. In ceramics I mainly work with porcelain casting slip and my fibers practice has been shifting towards soft sculpture made with found chiffon curtains. By letting both materials flow within my making process, I have found a balance in which my materials are informing one another and how I work with them. The fragility, rigidity, and permanence of clay directly contrasts the softness, ephemerality, and synthetic nature of the chiffon. Where both materials intersect is their fluidity and sheerness. I feel that these materials mirror each other in a pleasing and familial way. By applying light I feel that the work transforms and becomes a barricade separating the viewer from the light source while revealing the interiors of the sculptures.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: fibers